ʻAnusō̜n ngān phrarātchathān phlœ̄ng sop Nāng Wimon ʻAmāttayakun, na mēn Wat Makutkasattriyārām, Wanʻangkhān thī 2 Kanyāyon 2551. - Wimon ʻAmāttayakun, 1952-2008.; Suphakō̜n Rōtčhananin.; Phra ʻUbālīkhunūpamāčhān (Siričhanthō). ([Krung Thēp : Khrō̜pkhrūa Nāng Wimon ʻAmāttayakun], 2008)
Cremation volume for Wimon ʻAmāttayakun, 1952-2008; comprises biography and two articles on breast cancer and Buddhist sermons.
Keywords: Wimon ʻAmāttayakun, -- 1952-2008 -- Death and burial; Breast -- Cancer -- Popular works; Buddhist sermons, Thai